Higher Education Students’ Efforts to Overcome Internal Problems in the Academic Speaking Subject - Indah Sri Redjeki; Nurdayani Nurdayani; R. Muhajir; Nanik Retnowati (Lembaga Intelektual Muda (LIM) Maluku, 2023)
This study aimed to find information about students’ internal problems in the academic speaking subject as well as students’ efforts to overcome the problems. The participants in this study were students who had passed the subject in the 2018 academic year in a private university in Bogor. This study was a qualitative research by using questionnaires and interviews as research instruments to explore information related to the two research questions: 1) what are the students’ internal problems in the academic speaking subject? and 2) what are the students' efforts to overcome the problems? This study discovered four kinds of internal problems, namely: the problems in expressing ideas, applying correct grammar patterns, speaking anxiety, and low motivation. This study also discovered students’ efforts to overcome the problems, including preparing the material to be discussed, practicing speaking up with friends, practicing pronouncing English words correctly, learning grammar, vocabulary and pronunciation from grammar books, dictionary, and English learning applications. The findings of this study are expected to be useful, not only for students to keep doing the efforts in improving their speaking skills, but also for teachers to support students’ efforts to overcome the internal problems in the academic speaking subject